2020
DOI: 10.3390/su12124936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Two Strategies for the Collection of Wheat Residue after Mechanical Harvesting: Performance and Cost Analysis

Abstract: The growing population worldwide will create the demand for higher cereal production, in order to meet the food need of both humans and animals in the future. Consequently, the quantity of crop by-products produced by cereal cropping will increase accordingly, providing a good opportunity for fostering the development of the sustainable supply chain of renewable solid fuels and natural feedstock for animal farming. The conventional machineries used in wheat harvesting do not guarantee the possibility to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…The harvesting cost was assessed in 48.51 € ha −1 and 43.92 € Mg −1 FM which are consistent with the cost shown by Stolarski et al (2019) [41], but much lower than that calculated in a similar harvesting trial performed in Spain on camelina crop (65.97 € ha −1 and 69.42 € Mg −1 FM) [39]. Other trials performed on wheat and corn grain harvesting with combine harvester showed harvesting costs being 77.98 and 129.51 € ha −1 , respectively [46,61].…”
Section: Work Productivity and Costssupporting
confidence: 82%
See 2 more Smart Citations
“…The harvesting cost was assessed in 48.51 € ha −1 and 43.92 € Mg −1 FM which are consistent with the cost shown by Stolarski et al (2019) [41], but much lower than that calculated in a similar harvesting trial performed in Spain on camelina crop (65.97 € ha −1 and 69.42 € Mg −1 FM) [39]. Other trials performed on wheat and corn grain harvesting with combine harvester showed harvesting costs being 77.98 and 129.51 € ha −1 , respectively [46,61].…”
Section: Work Productivity and Costssupporting
confidence: 82%
“…Purchase and operating costs of the machinery were obtained interviewing the contractor, whilst the work productivity of the combine harvester was derived from the results of field tests and standard values for calculation were obtained from CRPA (Research Centre on Animal productions) methodology [45] as reported in Suardi et al (2020) [46][47][48].…”
Section: Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The EFC of 2.05 ha h −1 found in the present study is consistent with the EFC found in similar studies, but performed with the specific header, which reported values ranging from 1.57 to 2.10 ha h −1 [28][29][30]. In addition, the FE of 87.24% is also consistent with other tests performed on cereals harvesting, where the tested combine harvesters were all equipped with a dedicated header [38,50,51].…”
Section: Discussionsupporting
confidence: 92%
“…An interview with the contractor allowed identifying the purchase and operating costs of the combine harvester, while the performance of the machine was gained from the results of the field tests and used as input data. Finally, the standard values for calculation were taken from the CRPA (Research Centre on Animal productions) methodology [37], as applied in previous studies on a similar topic [38]. The hourly cost of the combine harvester was estimated taking into account the market value of the agricultural machinery.…”
Section: Estimation Of Harvesting Costsmentioning
confidence: 99%